Synthesis and properties of titanomagnetite (Fe3−xTixO4) nanoparticles: A tunable solid-state Fe(II/III) redox system - Pearce, C.I.; Qafoku, O.; Liu, J.; Arenholz, E.; Heald, S.M.; Kukkadapu, R.K.; Gorski, C.A.; Henderson, C.M.B.; Rosso, K.M. (Journal of colloid and interface science, 2012)
[Display omitted] ► Fe3−xTixO4 nanoparticles (10–12nm) synthesized by aqueous precipitation. ► Composition, structure, magnetic properties of Fe3−xTixO4 nanoparticles determined. ► Ti(IV) incorporation in the unit cell up to a limit of x⩽0.38. ► Nanoparticles with higher x had a minor amorphous secondary Fe(II)/Ti(IV) phase. ► Persistent segregation of Fe(II) to particle surfaces even after mild oxidation by dissolution. Titanomagnetite (Fe3−xTixO4) nanoparticles were synthesized by room temperature aqueous precipitation, in which Ti(IV) replaces Fe(III) and is charge compensated by conversion of Fe(III) to Fe(II) in the unit cell. A comprehensive suite of tools was used to probe composition, structure, and magnetic properties down to site-occupancy level, emphasizing distribution and accessibility of Fe(II) as a function of x. Synthesis of nanoparticles in the range 0⩽x⩽0.6 was attempted; Ti, total Fe and Fe(II) content were verified by chemical analysis. TEM indicated homogeneous spherical 9–12nm particles. μ-XRD and Mössbauer spectroscopy on anoxic aqueous suspensions verified the inverse spinel structure and Ti(IV) incorporation in the unit cell up to x⩽0.38, based on Fe(II)/Fe(III) ratio deduced from the unit cell edge and Mössbauer spectra. Nanoparticles with a higher value of x possessed a minor amorphous secondary Fe(II)/Ti(IV) phase. XANES/EXAFS indicated Ti(IV) incorporation in the octahedral sublattice (B-site) and proportional increases in Fe(II)/Fe(III) ratio. XA/XMCD indicated that increases arise from increasing B-site Fe(II), and that these charge-balancing equivalents segregate to those B-sites near particle surfaces. Dissolution studies showed that this segregation persists after release of Fe(II) into solution, in amounts systematically proportional to x and thus the Fe(II)/Fe(III) ratio. A mechanistic reaction model was developed entailing mobile B-site Fe(II) supplying a highly interactive surface phase that undergoes interfacial electron transfer with oxidants in solution, sustained by outward Fe(II) migration from particle interiors and concurrent inward migration of charge-balancing cationic vacancies in a ratio of 3:1.